Skyrmion Core Size Dependence as a Function of the Perpendicular Anisotropy and Radius in Magnetic Nanodots - Allende-Prieto, S; Castro-Barrera, M (Elsevier B.V., 2016)
A detailed analytical and numerical analysis of the skyrmion core size dependence as a function of the uniaxial perpendicular anisotropy and radius in magnetic nanodots has been carried out. Results from micromagnetic calculations show a non-monotonic behavior between the skyrmion core size and the uniaxial perpendicular anisotropy. The increment of the radius reduces the skyrmion core size at constant uniaxial perpendicular anisotropy. Thus, these results can be used for the control of the core sizes in magnetic artificial skyrmion crystals or spintronic devices that need to use a skyrmion configuration at room temperature. © 2016 Elsevier B.V. All rights reserved.
Keywords: Skyrmion; Perpendicular anisotropy; Dot